UNSETTLING SETTLER SHAME IN SCHOOLING: RE-IMAGINING RESPONSIBLE RECONCILIATION IN CANADA - Koelwyn, Ryan (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
This paper draws on “reintegrative shame” (engaging the offender(s) in discussions of the moral dimensions of the act), and scholars who position shame as transformative. This paper reasserts shame as an ethical matter arguing that reconciliation is a particular response to the historical shame generated from the establishment of the Indian Residential Schools in Canada. What would it mean to conceive of education as a site for working through shame? If we find a way to acknowledge our settler-shame, what might a responsible way of acting on it be? This paper considers these questions to present evidence for the importance of education as a space for making shame a social, ethical, and pedagogical project.